2013
DOI: 10.1021/ie303101n
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reforming of Glycerol in Supercritical Water over Bimetallic Pt–Ni Catalyst

Abstract: Catalytic reforming of pure glycerol for the production of hydrogen at low temperature and short residence times in supercritical water was investigated using a bimetallic Pt–Ni catalyst supported on alumina. Initial tests were carried out to study the reforming activity of bimetallic Pt–Ni catalysts by reforming different model compounds having different carbon numbers in supercritical water at 400–450 °C. The influence of different operating parameters such as reaction temperature, initial feed concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
(88 reference statements)
0
19
0
Order By: Relevance
“…15 Detailed information on and understanding of the effect of impurities on catalyst performance is crucial for the design of efficient catalysts for crude glycerol APR. For supercritical water reforming it was, for instance, reported that the use of crude glycerol led to rapid catalyst deactivation, which was not observed for runs with pure glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…15 Detailed information on and understanding of the effect of impurities on catalyst performance is crucial for the design of efficient catalysts for crude glycerol APR. For supercritical water reforming it was, for instance, reported that the use of crude glycerol led to rapid catalyst deactivation, which was not observed for runs with pure glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum supported on alumina (Pt/Al2O3) has been reported as active and selective catalyst in CAPR (Ciftci et al, 2012;Wen et al, 2010). To increase H2 production and selectivity, intensive studies on CAPR of glycerol (including other polyols, such as ethylene glycol) for H2 production over Pt-based bimetallic catalysts have also been conducted, such as Pt-Re (Ciftci et al, 2014;King et al, 2010;Kunkes et al, 2008), Pt-Co , and Pt-Ni bimetallic catalysts (Chakinala et al, 2013;El Doukkali et al, 2012;Tran and Kannangara, 2013;Tupy et al, 2013). Alloying Pt with Re showed improved C-C bond cleavage and glycerol conversion with relatively poor H2 selectivity (Ciftci et al, 2014;King et al, 2010;Kunkes et al, 2008 .…”
Section: Recommendations For Future Studymentioning
confidence: 99%
“…The objective of this work is to evaluate the ability of three common heat‐exchange strategies to transfer thermal energy to the dip‐tube salt separator in a way that results in effective separation of type‐1 salts. It should be mentioned that the separation of type‐1 salts pertains not only to the solar‐driven HTG of feedstock that contains mainly type‐1 salts (e.g., distiller's grain or crude glycerol); certain mixtures of type‐2 salts also exhibit an overall type‐1 phase behavior . The herein considered heat‐exchange strategies were based on transferring the thermal energy from hot air to the separator by using a bed of fluidized particles, axially finned tubes, or porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Theo bjective of this work is to evaluate the ability of three common heat-exchange strategies to transfert hermal energy to the dip-tubes alt separator in aw ay that results in effectives eparationo ft ype-1 salts.I ts hould be mentioned that the separation of type-1 salts pertains not only to the solar-drivenH TG of feedstock that contains mainly type-1 salts (e.g.,d istillersg rain [14] or crude glycerol [15] ); certain mixtureso ft ype-2 salts also exhibit an overall type-1 phase behavior. [12,16] Theh erein considered heat-exchange strategies were basedo nt ransferring the thermal energy from hot air to the separator by using ab ed of fluidized particles, axially finned tubes,o rp orous media.P reliminaryd esign of different configurations of these three HX types (where a configurationr efers to aH Xw ith defined geometry,d imensions,a nd operating conditions) were carried out using simple engineeringc alculationsr equiring only two inputs: (i)the axial temperature profile at the HSI and (ii)the heattransferr ate to the HSI.…”
Section: Introductionmentioning
confidence: 99%